The RNA Helicase BELLE Is Involved in Circadian Rhythmicity and in Transposons Regulation in Drosophila melanogaster - Cusumano, Paola; Damulewicz, Milena; Carbognin, Elena; Caccin, Laura; Puricella, Antonietta; Specchia, Valeria; Bozzetti, Maria Pia; Costa, Rodolfo; Mazzotta, Gabriella M. (Frontiers in Physiology, 2019)
Circadian clocks control and synchronize biological rhythms of several behavioral and physiological phenomena in most, if not all, organisms. Rhythm generation relies on molecular auto-regulatory oscillations of interlocked transcriptional-translational feedback loops. Rhythmic clock-gene expression is at the base of rhythmic protein accumulation, though post-transcriptional and post-translational mechanisms have evolved to adjust and consolidate the proper pace of the clock. In Drosophila, BELLE, a conserved DEAD-box RNA helicase playing important roles in reproductive capacity, is involved in the small RNA-mediated regulation associated to the piRNA pathway. Here we report that BELLE is implicated in the circadian rhythmicity and in the regulation of endogenous transposable elements (TEs) in both nervous system and gonads. We suggest that BELLE acts as important element in the piRNA-mediated regulation of the TEs and raise the hypothesis that this specific regulation could represent another level of post-transcriptional control adopted by the clock to ensure the proper rhythmicity.